BSR guideline on the management of adults with systemic lupus erythematosus (SLE) 2018: baseline multi-centre audit in the UK. (8th December 2020) - Pearce, Fiona A; Rutter, Megan; Sandhu, Ravinder; Batten, Rebecca L; Garner, Rozeena; Little, Jayne; Narayan, Nehal; Sharp, Charlotte A; Bruce, Ian N; Erb, Nicola; Griffiths, Bridget; Guest, Hannah; et al.
Abstract: Objectives: To assess the baseline care provided to patients with SLE attending UK Rheumatology units, audited against standards derived from the recently published BSR guideline for the management of adults with SLE, the NICE technology appraisal for belimumab, and NHS England's clinical commissioning policy for rituximab. Methods: SLE cases attending outpatient clinics during any 4-week period between February and June 2018 were retrospectively audited to assess care at the preceding visit. The effect of clinical environment (general vs dedicated CTD/vasculitis clinic and specialized vs non-specialized centre) were tested. Bonferroni's correction was applied to the significance level. Results: Fifty-one units participated. We audited 1021 episodes of care in 1003 patients (median age 48 years, 74% diagnosed >5 years ago). Despite this disease duration, 286 (28.5%) patients had active disease. Overall in 497 (49%) clinic visits, it was recorded that the patient was receiving prednisolone, including in 28.5% of visits where disease was assessed as inactive. Low documented compliance (<60% clinic visits) was identified for audit standards relating to formal disease-activity assessment, reduction of drug-related toxicity and protection against comorbidities and damage. Compared with general clinics, dedicated clinics had higher compliance with standards for appropriate urine protein quantification (85.1% vs 78.1%, P  ≤ 0.001). Specialized centres had higher compliance with BILAG Biologics Register recruitment (89.4% vs 44.4%, P  ≤ 0.001) and blood pressure recording (95.3% vs 84.1%). Conclusions: This audit highlights significant unmet need for better disease control and reduction in corticosteroid toxicity and is an opportunity to improve compliance with national guidelines. Higher performance with nephritis screening in dedicated clinics supports wider adoption of this service-delivery model.